A population‑based propensity score matching analysis of neoadjuvant compared to adjuvant chemotherapy in luminal breast cancer - Zheng, Chenhui; Zheng, Danni; Zhang, Yuzhu; Lin, Renzhi; Zheng, Zhibao (Scientific reports, 2025)
This study evaluated the long-term prognosis of patients with luminal (HR+/HER2−) breast cancer who underwent either neoadjuvant or adjuvant chemotherapy. Between January 2014 and December 2018, 1065 h+/HER2− breast cancer patients were retrospectively analyzed. Each patient receiving neoadjuvant chemotherapy was matched with two patients receiving adjuvant chemotherapy using a 1:2 propensity score matching (PSM) approach. After matching, 47 neoadjuvant chemotherapy patients and 89 adjuvant chemotherapy patients were included. The clinical and pathological characteristics of both groups were compared, and risk factors for postoperative events were assessed alongside a survival analysis. Following propensity score matching, the characteristics of the two groups were well balanced. The study identified lower progesterone receptor (PR) expression, histological grade III, and lymph node metastasis as independent risk factors for recurrence-free survival (RFS). No significant difference in RFS was observed between neoadjuvant and adjuvant chemotherapy. It is recommended that patients with HR+/HER2− breast cancer who exhibit a poor response to neoadjuvant chemotherapy should undergo early surgery, with personalized treatment decisions based on postoperative pathological findings.